Forage legumes in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Potentials of forage legumes in farming systems of sub-Saharan Africa / Haque. I., et al. (eds.). 1986 ILCA, Addis Ababa, 569 pp. ISBN 92-9053-080-4 [workshop proceedings]